Tooth Contact Analysis of Straight Bevel Gears Machined with Concave Cutters - Wang Zhiyong; Zhang Zhu; Duan Zhihong; Zhang Yu (Jixie chuandong)
In order to use the concave cutter to process the straight bevel gear on the domestic CNC spiral bevel gear machine tool, the principle of using the concave cutter to process the straight bevel gear and the TCA method of tooth surface contact analysis are studied. Based on the machining principle and structural characteristics of the concave cutter, the tooth surface mathematical model of the straight bevel gear machined by the concave cutter is established, and the corresponding tooth surface contact analysis method is given. The tooth contact analysis program is compiled, and the contact pattern and transmission error curve of the gear pair are calculated. The correctness of the tooth surface mathematical model and the TCA method of tooth surface contact analysis are verified by the actual tooth cutting and contact spot inspection. It provides a theoretical basis for the determination of bevel gear machining parameters, tool parameters and the meshing quality control.